2018
DOI: 10.1016/j.devcel.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Inhibition Mediates Apoptosis Sensitization in Cancer Therapy by Relieving FOXO3a Turnover

Abstract: Macroautophagy (autophagy) is intimately linked with cell death and allows cells to evade apoptosis. This has prompted clinical trials to combine autophagy inhibitors with other drugs with the aim of increasing the likelihood of cancer cells dying. However, the molecular basis for such effects is unknown. Here, we describe a transcriptional mechanism that connects autophagy to apoptosis. The autophagy-regulating transcription factor, FOXO3a, is itself turned over by basal autophagy creating a potential feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 25 publications
9
136
0
Order By: Relevance
“…Cancer is frequently a result of disrupted coordination between the suppressive signals from internal or external stresses and the stimulating signals from growth factors and nutrients (34). The mTOR signaling is a key regulator involved in many facets of carcinogenic and metabolic events, including autophagy, apoptosis (35)(36)(37)(38)(39)(40)(41), migration and invasion (42), differentiation, energy metabolism, and inflammation (43). Autophagy is a stress-responsive catabolic process followed by lysosomal degradation of intracellular components (44), removing aggregated protein, damaged organelles, and pathogen clearance, in order to provide energy for normal cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is frequently a result of disrupted coordination between the suppressive signals from internal or external stresses and the stimulating signals from growth factors and nutrients (34). The mTOR signaling is a key regulator involved in many facets of carcinogenic and metabolic events, including autophagy, apoptosis (35)(36)(37)(38)(39)(40)(41), migration and invasion (42), differentiation, energy metabolism, and inflammation (43). Autophagy is a stress-responsive catabolic process followed by lysosomal degradation of intracellular components (44), removing aggregated protein, damaged organelles, and pathogen clearance, in order to provide energy for normal cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the aberrant regulation of apoptosis results in uncontrolled cell proliferation . As PLAC8 overexpression facilitates BC cell proliferation, we assessed whether increased or decreased PLAC8 expression contributes to cell apoptosis to influence BC progression.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the aberrant regulation of apoptosis results in uncontrolled cell proliferation. [20][21][22] As PLAC8 overexpression facilitates BC cell proliferation, we assessed whether increased or decreased PLAC8 expression contributes to cell apoptosis to influence BC progression. The results revealed that PLAC8transfected T47D cells were inhibited for apoptosis, whereas PLAC8 knockdown significantly induced apoptosis in Bcap-37 cells ( Figure 4A,B).…”
Section: Plac8 Silencing Induces Caspase 3/9 Activation Bcl-2 Up-rmentioning
confidence: 99%
“…Interestingly, recent work from Thorburn et al . shows that autophagy can regulate apoptosis by degrading cytoplasmic FOXO3A . Therefore, these results regarding the link between autophagy, FOXO3A and the maintenance of LSCs warrant further investigation.…”
Section: Role and Regulation Of Autophagy In CML And Lscsmentioning
confidence: 85%